Prediction of axial limit capacity of stone columns using dimensional analysis - Nazaruddin A.T.; Mohamed Z.; Mohd Azizul L.; Hafez M.A. (American Institute of Physics Inc., 2023)
Stone column is the most favorable method used by engineers in designing work for stabilization of soft ground for road embankment, and foundation for liquid structure. Easy installation and cheaper cost are among the factors that make stone column more preferable than other method. Furthermore, stone column also can acts as vertical drain to increase the rate of consolidation during preloading stage before construction work started. According to previous studied there are several parameters that influence the capacity of stone column. Among of them are angle friction of among the stones, arrangement of column (two pattern arrangement most applied triangular and square), spacing center to center between columns, shear strength of soil, and physical size of column (diameter and length). Dimensional analysis method (Buckingham-Pi Theorem) has used to carry out the new formula for prediction of load capacity stone columns. Experimental data from two previous studies was used for analysis of study. 2017 Author(s).